Roommate - Alvarez, Maria Astrid A. 1985- (Quezon City College of Mass Communication, University of the Philippines Diliman, 2006)
"Human mins is a complex thing to deal with. And in our film Rommate, we used it as an instrument to show the complex situation the main character is going through. We let her inner thoughts and feelings came into life through the character of another person she created. The wishes which underlie this reshaping of reality are often completely unconscious and it set up inner conflicts to the mind which seeks to defend itself by all kind of means, among which is the creations of another self or personality. Also Roommate is a representation of what Althusser defines as Repressive State Apparatuses (RSA). She was in that complex situation because she was forced to follow and obey her mother's mandate, otherwise she will be punished."
Vita.
Thesis (A.B. Film and Audiovisual Communication)--University of the Philippines Diliman